Immediate and postponed results of resection interventions in pulmonary tuberculosis patients with local inflammatory changes in the bronchial tree - Zh. A. Laushkina; S. V. Sklyuev; D. V. Krasnov; D. A. Skvortsov; N. V. Stavitskaya (Туберкулез и болезни лёгких)
The objective: to study the frequency and nature of postoperative complications, immediate and postponed results of resection interventions in pulmonary tuberculosis patients depending on the presence and pathomorphological parameters of local infl ammatory changes in the bronchial tree.Subjects and Methods. 147 pulmonary tuberculosis patients who underwent pulmonary resection were enrolled in the prospective cohort study. Main Group (n=49) included patients with local infl ammatory changes in the bronchi before surgery; Comparison Group (n=98) included patients with no infl ammatory changes in the bronchi.Results. The presence of local infl ammatory changes in the bronchial tree detected by bronchoscopy, did not have a signifi cant impact on the development of complications during surgical treatment - neither on their number nor on structure. The incidence of complications of resection interventions depends on severity of tuberculosis lesions in the lung.